2021
DOI: 10.1029/2020gc009438
|View full text |Cite
|
Sign up to set email alerts
|

Amphibious Shear Wave Structure Beneath the Alaska‐Aleutian Subduction Zone From Ambient Noise Tomography

Abstract: The Alaska-Aleutian subduction zone along the southern margin of Alaska is a tectonically active region with on-going underthrusting of Pacific plate and collisional orogeny produced by the Yakutat microplate (e.g., Eberhart-Phillips et al., 2006). It is a region where North America's largest megathrust earthquakes and powerful volcanic eruptions occur. The subduction zone exhibits remarkable along-strike variations in seismicity and slip deficit; and the physical link between plate fabric, hydration, and eart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 50 publications
(144 reference statements)
2
18
0
Order By: Relevance
“…Beneath the Shumagin Gap, the slab velocity decreases significantly and widely, whereas the velocity reduction is not equivalent beneath the Semidi and Kodiak segments. This notable feature is consistent with the previous results of 2-D OBS wide-angle reflection/refraction surveys across the Shumagin Gap and Semidi segment (Shillington et al, 2015) and a large-scale Vs model obtained by ambient noise tomography (Feng, 2021). Above the velocity reduction zone of the subducting slab, prominent low-velocity (low-V) and high Vp/Vs anomalies are visible in the forearc overriding crust beneath the Shumagin Gap and the western portion of the 1938 rupture zone (Figure 6, Figures S22 and S23 in Supporting Information S1).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Beneath the Shumagin Gap, the slab velocity decreases significantly and widely, whereas the velocity reduction is not equivalent beneath the Semidi and Kodiak segments. This notable feature is consistent with the previous results of 2-D OBS wide-angle reflection/refraction surveys across the Shumagin Gap and Semidi segment (Shillington et al, 2015) and a large-scale Vs model obtained by ambient noise tomography (Feng, 2021). Above the velocity reduction zone of the subducting slab, prominent low-velocity (low-V) and high Vp/Vs anomalies are visible in the forearc overriding crust beneath the Shumagin Gap and the western portion of the 1938 rupture zone (Figure 6, Figures S22 and S23 in Supporting Information S1).…”
Section: Resultssupporting
confidence: 92%
“…Previous studies suggest that the subducting slab in the study area may have significant lateral variations in hydration and dehydration states. Prominent seismic velocity reduction is imaged in the uppermost mantle of the subducting Pacific plate beneath the Shumagin Gap, while it is not revealed beneath the neighboring Semidi segment (Feng, 2021; Shillington et al., 2015). As multi‐channel seismic reflection and bathymetric studies suggested, the along‐trench variations of seismic velocity may result from different development degrees of normal faults caused by the plate bending in outer‐rise areas before subduction (J. Li et al., 2018; Shillington et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…By combining ambient noise techniques, dispersion curve analysis of Rayleigh waves, 2-D tomographic inversion of traveltimes and 1-D depth inversion of dispersion curve data we derived an amphibious 3-D Vs model. While most of the ANT studies focus on continental structures, only a few involve ocean bottom seismographs or amphibious seismic instrumentation targeting marine structures and/or transitions into the continent (Harmon et al 2007;Yao et al 2011;Zha et al 2014;Gao & Shen 2015;Ball et al 2016;Corela et al 2017;Lynner & Porritt 2017;Ryberg et al 2017;Hable et al 2019;Guerin et al 2020;Feng 2021;Li et al 2021;Wolf et al 2021;Yamaya et al 2021). We follow the method described by Ryberg et al (2016bRyberg et al ( , 2017 to derive fundamental mode Rayleigh waves between station pairs from ambient seismic noise (Campillo & Paul 2003;Shapiro et al 2005;Schuster 2009;Campillo & Roux 2014).…”
Section: Data a C Q U I S I T I O N A N D P Ro C E S S I N Gmentioning
confidence: 99%
“…In this paper, we employed CCP stacking of Sp converted phases to study lithospheric and asthenospheric properties near the subduction zone and across the continental lithosphere beneath the state of Alaska. Prior studies have imaged mantle discontinuities beneath Alaska using Sp (Bauer et al., 2014; O’Driscoll & Miller, 2015) and Ps (Bauer et al., 2014; Chuang et al., 2017; Mann et al., 2022; Rondenay et al., 2008, 2010) phases; explored upper and subducting plate crustal structure with Ps data (Allam et al., 2017; Brennan et al., 2011; Ferris et al., 2003; Kim et al., 2014; Miller & Moresi, 2018; Miller et al., 2018; Rondenay et al., 2008, 2010; Veenstra et al., 2006; Zhang et al., 2019); and incorporated Sp (Gama et al., 2021) or Ps (Berg et al., 2020; Feng, 2021; Martin‐Short et al., 2018; Ward & Lin, 2018) data in joint inversions with surface waves. However, to our knowledge this is the first study to comprehensively map crust and mantle discontinuities in Alaska with Sp phases recorded by the U.S. National Science Foundation (NSF) EarthScope Transportable Array (TA).…”
Section: Introductionmentioning
confidence: 99%